STUDI PENCIPTAAN KARYA SENI INSTALASI “MARI KITA…!” - Isnanta, Satriana Didiek; Zarkasi, Much. Sofwan; Panindias, Asmro Nurhadi (Institut Seni Indoensia Surakarta, 2020)
ABSTRACTThis article is the result of a study on the creation of installation art based on local wisdom with the source of the idea of creating the Loro Blonyo statue. Loro blonyo is a pair of wooden statues consisting of a statue of a woman accompanied by a man wearing a traditional Javanese wedding dress in a basahan style in a sitting position. Broadly speaking, the meaning of the Loro Blonyo statue for the Javanese community is the unity of a couple as a reflection of the harmony and unity of Javanese thoughts. The meaning of the loro blonyo statue is then analyzed, elaborated, and reinterpreted.The research method used is Dharsono's Artistik Creation (2016), namely: research with an ethical approach and research with an emic approach, exploration, experimentation, and formation. The results of the research were concluded and became the basis for the concept of installation art with the visual form of local culture as a strengthening of cultural identity. Keywords: installation art, art experimentation, loro blonyo, cultural identity. ABSTRAKArtikel ini merupakan hasil studi penciptaan karya seni instalasi berbasis kearifan lokal dengan sumber ide penciptaan patung Loro Blonyo. Loro blonyo adalah sepasang patung dari bahan kayu yang terdiri atas patung perempuan dan didampingi seorang laki-laki dengan menggunakan busana perkawinan adat Jawa gaya basahan dalam posisi duduk. Secara luas, makna patung Loro Blonyo bagi masyarakat Jawa adalah kesatuan pasangan sebagai refleksi pikiran Jawa yang harmoni dan manunggal. Makna patung loro blonyo tersebut kemudian dianalisis, dielaborasi dan ditafsir ulang.Metode penelitian menggunakan Kreasi Artisik Dharsono (2016), yaitu : riset dengan pendekatan etik dan riset dengan pendekatan emik, eksplorasi, eksperimentasi dan pembentukan. Hasil riset tersebut disimpulkan dan menjadi dasar konsep karya seni instalasi dengan wujud visual budaya lokal sebagai penguatan identitas kultural. Kata kunci: Seni instalasi, eksperimentasi seni, loro blonyo, identitas kultural.